Konsep Pendidikan Islam Inklusi untuk Membangun Pendidikan yang Bermartabat dan Tidak Dikotomi - Nanang Budianto (STAIFAS-Press, 2016)
Inclusive education is believed by most experts and practitioners in the field of education to achieve Education for All (EFA). Said that because of this paradigm is very accommodating to all of the different conditions of learners, good learners conditions related to the physical, mental, and social. The difference is common / reasonable, because in reality every man is different. The difference will not be possible to be eliminated, but usually only be facilitated to be developed in accordance with the potential of each. The difference should not be a barrier to it together, but it made a difference in wealth and power to achieve educational achievement (change in behavior towards the better). Inclusive education is education that is open and friendly towards learning by promoting actions to appreciate and embrace the differences. Therefore, inclusive education is understood as an approach that seeks to transform the education system by eliminating barriers that could hinder each individual student to participate fully in the education that comes with support services.